Pengaruh Doomscrolling terhadap Kecemasan Mahasiswa Fakultas Dakwah dan Ilmu Komunikasi UIN Jakarta - Najla Nazihah; Nur Najmi Laila; Hilda Natasya; Siti Zakiatul; Harianti Fauziyatul (Lembaga Pengembangan Kinerja Dosen, 2025)
The growth of digital technology has made it easier to access information quickly and flexibly, anytime and anywhere. However, this convenience also gave birth to a new behavior called doomscrolling, which is the tendency of individuals to constantly scroll and consume negative content on social media, which has the potential to affect users' psychological conditions, including anxiety. This study was conducted to examine the extent to which doomscrolling activity is related to the level of anxiety experienced by students of the Faculty of Da'wah and Communication Sciences (FDIKOM) UIN Syarif Hidayatullah Jakarta. The design is quantitative correlational to examine the relationship between variables. A total of 30 respondents were involved through purposive sampling technique, based on certain predetermined criteria. The research instrument was a closed questionnaire with a Likert scale (1-5), which had previously gone through a validity test process to ensure its feasibility. The results of linear regression analysis showed a significant influence between doomscrolling and anxiety, with a coefficient of determination (R²) of 0.335. This means that doomscrolling contributes 33.5% to student anxiety, while 66.5% is influenced by other factors. This finding confirms that doomscrolling behavior influenced by psychological, social, and technological factors can increase anxiety if not addressed wisely. This study recommends the importance of.